Giant aneurysm of the right internal carotid artery in an 8-month-old child presenting with a persistent red eye. Issue 1 (February 2016) - Almohiy, H.; Alamri H, A.; Saade, C.
Abstract: Summary: Childhood intracranial aneurysms are a rare entity. Diagnosis of intracranial aneurysms in infancy may be difficult because of their infrequency and confusing clinical presentation. Findings with routine radiographic methods may be misleading and difficult to interpret. This case report entails a giant aneurysm arising from the right internal carotid artery (RICA) in an 8-month-old child. Highlights: Measuring the exact contrast media transit time of large paediatric aneurysm. Matching contrast media delivery with aneurysmal filling. Demonstrate that MDCT angiography is crucial in the diagnosis and selection of surgical outcomes in life-threatening conditions.